AngioVac System Used for Vegetation Debulking in a Patient with Tricuspid Valve Endocarditis: A Case Report and Review of the Literature. (7th November 2017) - Abubakar, Hossam; Rashed, Ahmed; Subahi, Ahmed; Yassin, Ahmed S.; Shokr, Mohamed; Elder, Mahir
Abstract : AngioVac is a vacuum-based device approved in 2014 for percutaneous removal of undesirable materials from the intravascular system. Although numerous reports exist with regard to the use of the AngioVac device in aspiration of iliocaval, pulmonary, upper extremity, and right-sided heart chamber thrombi, very few data are present demonstrating its use in treatment of right-sided endocarditis. In this case report, we describe the novel device used in debulking a large right-sided tricuspid valve vegetation reducing the occurrence of septic embolisation and enhancing the efficacy of antibiotics in clearance of bloodstream infection. Further research is needed in larger RSIE patient populations to confirm the benefits and the potential of improved outcomes associated with the AngioVac device as well as identify its potential complications.